A retrospective study about the trend analysis of Industrial accidents in Pakistan - Mohsin Abbas; Balkhyour A Mansour (Occupational Health and Safety Society of Nepal, 2017)
Background: Occupational accidents in developing countries like Pakistan are obvious due to poor occupational health safety infrastructure. Objective: This retrospective study aimed to analyze the industrial accidents in factories of Pakistan during 1993-2009. Methods and Material: An index value calculation method used to investigate the trends of occupational accidents. Accident rate (103), fatal accident rate (105), and non-fatal accident rate (103) were also calculated. Pakistan Statistical Year Books published by Pakistan Bureau of Statistics (PBS) used as data source. Results: Data of total 10330 industrial accidents analyzed and decreasing accident rate found with average 3.1 accident per 103 factory workers. Fatal accident increased with an average of 23 fatal accidents per 105 factories workers. Regarding the severity of industrial accidents, minor accidents found at 74% followed by serious (18%) and fatal accidents (8%). Decreased trends of index values and accident rates can associate with the increased human development index of Pakistan, but increased fatal accidents in factories and under-reporting are major areas of concern for safety stakeholders. Conclusions: Despite industrial accidents decreased in factories but more in depth studies with more recent data about the root causes of accidents can be useful to draw a true picture of occupational accidents in Pakistan. Improved social security system in Pakistan can be helpful to the exact recording of occupational accidents data.